2015
DOI: 10.26623/jdsb.v17i1.505
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Dampak Pembangunan Infrastruktur Jalan Terhadap Pertumbuhan Usaha Ekonomi Rakyat Di Kota Semarang

Abstract: This study aims to analyze the impact of road construction on the growth of economic enterprises, income people, social benefits and economic benefits received by the people of the city of Semarang. The target sample is a community business owners, which is based on the degree of homogeneity of society and livelihoods, using purposive sampling technique. Data collected through questionnaires and focus group discussion ( FGD ), with descriptive analysis method, and the analysis of SPSS .Based on the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
0
6
0
13
Order By: Relevance
“…Through the lecturing approach (lecture) and Focus Group Discussion (FGD), the author used in the delivery of training materials so that participants were more involved and connected with one another. This method is considered capable of providing a better exploratory understanding for all participants (NSS et al, 2015). The power of data exploration is the advantage of qualitative methods over quantitative methods (Maxwell & Reybold, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Through the lecturing approach (lecture) and Focus Group Discussion (FGD), the author used in the delivery of training materials so that participants were more involved and connected with one another. This method is considered capable of providing a better exploratory understanding for all participants (NSS et al, 2015). The power of data exploration is the advantage of qualitative methods over quantitative methods (Maxwell & Reybold, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Menurut Indriantoro (2001:145) data subjek merupakan jenis data penelitian yang berupa opini, sikap, pengalaman, atau karakteristik dari seseorang atau sekelompok orang yang menjadi subyek penelitian. Data yang digunakan adalah dari hasil jawaban responden atas pertanyaan yang diajukan penulis kepada responden dalam bentuk kuesioner/tulisan [12]. Di Dalam pengumpulan data,sumber data yang diperlukan adalah sebagai berikut :(Arikunto, 2001 :48) adalah data primer dimana data yang diperoleh secara langsung dari sumbernya, diamati, dan dicatat untuk pertama kalinya.…”
Section: Metodologi ➢ Jenis Data Dan Sumberdataunclassified
“…An analysis of the impact of road construction conducted by NSS et al concluded that the construction of road infrastructure has a positive and significant effect on the economic benefits of community economic efforts. When road construction is carried out, the changes that occur in the economy of the community will run in the direction of the development (NSS et al, 2015).…”
Section: • Impact Of Road Infrastructure Development On Economic and Social Transformationmentioning
confidence: 99%